Current occupational therapy and physiotherapy practice in implementing home programmes for young children with cerebral palys in South Africa - Davies, Lauren (My University, 2016)
Cerebral palsy (CP) is a non-progressive permanent disorder of movement that can cause varying limitations in activity participation and function. The current practice of home programmes for young children diagnosed with CP as understood and implemented by paediatric occupational and physiotherapists in five service delivery settings in South Africa was investigated. Forty-eight participants completed an online questionnaire regarding the content, design and implementation of home programmes they prescribe. Fifteen of these participants then took part in semi structured interviews. The findings were compared to the model home programme developed by Novak and Cusick. Results revealed that home programmes within the private sector were comparable to the model, but that there were aspects in resourced constrained settings that led to differences. Collaborative relationships between therapists and parents/caregivers were especially challenging and affected the preceding phases of the model. Recommendations in the form of a South African home programme model are made.
A dissertation submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. 2016